A Validated Model for Individualized Prediction of Live Birth in Patients With Adenomyosis Undergoing Frozen–Thawed Embryo Transfer - Wu, Yaoqiu; Yang, Rong; Lin, Haiyan; Cao, Chunwei; Jiao, Xuedan; Zhang, Qingxue (Frontiers in Endocrinology, 2022)
Purpose: To develop a predictive tool for live birth in women with adenomyosis undergoing IVF/ICSI treatment. Methods: A total of 424 patients with adenomyosis underwent frozen-thawed embryo transfer (FET) from Jan 2013 to Dec 2019 at a public university hospital were included. The patients were randomly divided into training (n = 265) and validation (n = 159) samples for the building and testing of the nomogram, respectively. Multivariate logistic regression (MLR) was developed on the basis of clinical covariates assessed for their association with live birth. Results: In all, 183 (43.16%) patients became pregnant, and 114 (26.88%) had a live birth. MLR showed that probability of live birth was significantly correlated with the age (odds ratio [OR], 3.465; 95% confidence interval [CI], 1.215-9.885, P = 0.020), uterine volume (OR, 8.141; 95% CI, 2.170 - 10.542; P = 0.002), blastocyst transfer (OR, 3.231; 95% CI, 1.065 - 8.819, P = 0.023), twin pregnancy (OR, 0.328; 95% CI, 0.104-0.344, P = 0.005) and protocol in FET (P < 0.001). The statistical nomogram was built based on age, uterine volume, twin pregnancy, stage of transferred embryo and protocol of FET, with an area under the curve (AUC) of 0.837 (95% CI: 0.741 - 0.910) for the training cohort. The AUC for the validation cohort was 0.737 (95% CI: 0.661 - 0.813), showing a satisfactory goodness-of-fit and discrimination ability in this nomogram. Conclusions: The user-friendly nomogram built on the risk factors of live birth in patients with adenomyosis, provides a useful guide for medical staff on individualized decisions making during the IVF/ICSI procedure.